2010
DOI: 10.1016/j.cplett.2010.07.054
|View full text |Cite
|
Sign up to set email alerts
|

End-point calculation of solvation free energy of amino-acid analogs by molecular theories of solution

Abstract: The computational efficiency is improved for the solvation free energy when the calculation is restricted to the initial and final states of the solute insertion process (pure solvent and solution systems of interest). We explore the possibility of such 'end-point' calculations and assess the performance of several approximate free-energy functionals against benchmarks for amino-acid analogs in water. The performance is the best and the second, respectively, for the method of energy representation and the RISM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 48 publications
(101 reference statements)
2
68
0
Order By: Relevance
“…The molecular flexibility and the system inhomogeneity are handled without any modification of the method since the projection of solutesolvent configuration is done in terms of energy; the flexibility and inhomogeneity are spatial information, which are to be projected out in the formulation. Through combination with molecular simulation, the error due to the approximation in the method is observed to be not larger than the error due to the use of force field, 317 though the computational speed is inferior to those of (1D) RISM-based schemes. The energy-representation method provides a universal computational and theoretical platform for calculation of thermodynamic parameters of solvation and has been already applied to a range of different systems: supercritical fluids, air-water interfaces, micelles, lipid membranes, proteins, and QM/MM systems.…”
Section: Note On Alternative Distribution-function Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular flexibility and the system inhomogeneity are handled without any modification of the method since the projection of solutesolvent configuration is done in terms of energy; the flexibility and inhomogeneity are spatial information, which are to be projected out in the formulation. Through combination with molecular simulation, the error due to the approximation in the method is observed to be not larger than the error due to the use of force field, 317 though the computational speed is inferior to those of (1D) RISM-based schemes. The energy-representation method provides a universal computational and theoretical platform for calculation of thermodynamic parameters of solvation and has been already applied to a range of different systems: supercritical fluids, air-water interfaces, micelles, lipid membranes, proteins, and QM/MM systems.…”
Section: Note On Alternative Distribution-function Approachesmentioning
confidence: 99%
“…136 For a test set of 19 organic solutes studied in this work, 136 the 1D RISM/PWC free energy functional provided better agreement with experimental data than the original 1D RISM/PW model. 136,316,317 In its current state, however, the 1D RISM/PWC model is not suitable for many polyfunctional organic solutes due to its limited parameterization and it therefore requires further development.…”
Section: Improvement Of Sfe Predictions With a Volume Correctionmentioning
confidence: 99%
“…In the energy-representation method, the simulation is performed only for the pure solvent and solution systems, and a set of energy distribution functions obtained provides the solvation free energy through an approximate functional. [7][8][9][10] It was observed that the error caused by the use of the approximate functional is not larger than the error due to the use of force field 16 and that the solvation free energy of a protein with a few hundred residues can be feasibly evaluated. 17 In the present work, we investigate the relationship between the protein structure (conformation) and the hydration a) Electronic mail: nobuyuki@scl.kyoto-u.ac.jp.…”
mentioning
confidence: 99%
“…[32][33][34][35] For both HNC and its n-order expansions, the excess chemical potential of the solute at infinite dilution, µ ex , can be derived from the RISM solute-solvent correlation functions. 14,30,[36][37][38] For the HNC closure, the functional is 14…”
Section: Theorymentioning
confidence: 99%